FlyBase--the Drosophila database. The FlyBase Consortium. (1994)
FlyBase is a database of genetic and molecular data concerning Drosophila. FlyBase is maintained as a relational database (in Sybase) and is available from the ftp.bio.indiana.edu Gopher server. The scope of FlyBase includes: genes, alleles, aberrations, pointers to sequence data, stock lists, Drosophila workers and bibliographic references.